2012
DOI: 10.1016/s1001-0742(11)60861-9
|View full text |Cite
|
Sign up to set email alerts
|

Spatial distribution of archaeal and bacterial ammonia oxidizers in the littoral buffer zone of a nitrogen-rich lake

Abstract: The spatial distribution and diversity of archaeal and bacterial ammonia oxidizers (AOA and AOB) were evaluated targeting amoA genes in the gradient of a littoral buffer zone which has been identified as a hot spot for N cycling. Here we found high spatial heterogeneity in the nitrification rate and abundance of ammonia oxidizers in the five sampling sites. The bacterial amoA gene was numerically dominant in most of the surface soil but decreased dramatically in deep layers. Higher nitrification potentials wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
1
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 44 publications
1
12
1
2
Order By: Relevance
“…The effect of plant rhizosphere on AOA and AOB abundance remain inconclusive based on previous studies . In this study, we found that the B amo A/A amo A ratios were higher on root surfaces than in bulk soil of most samples in summer, which was similar with the result from Trias et al .…”
Section: Discussionsupporting
confidence: 91%
“…The effect of plant rhizosphere on AOA and AOB abundance remain inconclusive based on previous studies . In this study, we found that the B amo A/A amo A ratios were higher on root surfaces than in bulk soil of most samples in summer, which was similar with the result from Trias et al .…”
Section: Discussionsupporting
confidence: 91%
“…However, other researchers observed that AOB outnumbered AOA in nitrogen-rich sediments and in agricultural soils (Jia & Conrad, 2009;Wang et al, 2011;Wang et al, 2012). In this study, we found that AOA were much more abundant than AOB (by two or three orders of magnitude) and played an important role in ammonia oxidation.…”
Section: Discussioncontrasting
confidence: 41%
“…Previous studies reported that AOA was the dominant taxon among the ammonia‐oxidizing prokaryotes in soils and marine ecosystems with low ammonium concentrations (Leininger et al., ; Wuchter et al., ). However, other researchers observed that AOB outnumbered AOA in nitrogen‐rich sediments and in agricultural soils (Jia & Conrad, ; Wang et al., ; Wang et al., ). In this study, we found that AOA were much more abundant than AOB (by two or three orders of magnitude) and played an important role in ammonia oxidation.…”
Section: Discussionmentioning
confidence: 89%
“…The boundary or ecotone between two features in a landscape, for example the land/freshwater interface, is often the biogeochemical hot spot (McClain et al ., ; Wang et al ., ,c; Zhu et al ., ). Rice paddy fields are dry‐wet alternation ecosystems, resulting in the soil/water ecotones which are ideal environments for soil microorganisms (Ishii et al ., ).…”
Section: Introductionmentioning
confidence: 99%